Sistema preventivo, educação social e ecologia integral: entrelaces contemporâneos para a educação salesiana - Rodrigues, Celene Couto (2023)
Education is fundamentally social, as it is part of the construction of society and takes place in different contexts, formal and informal, historical and social, through teaching and learning processes that promote the development of human beings. Our goal in this dissertation is to contribute to the epistemological construction of philosophical and methodological elements of the interweaving of the Preventive System of Don Bosco, the Social Education and Integral Ecology. Our hypothesis is based on the assumption that Social, Preventive, and Integral are established categories when analyzing the theories of Salesian education. The question that drives this research is: What elements of the Preventive System do we find as references to the possibilities of developing educational processes in the light of Integral Ecology and which contribute to the Salesian Social Education? In order to analyze this correlation, four objectives were developed, very clearly and defined, namely: (i) Understanding the concept and relevance of Social Education as presence in the field of Education in the 21st century; (ii) Describing the Preventive System proposed by Don Bosco as a Salesian educational philosophy; (iii) Understanding the concept of Integral Ecology with formative/educational perspectives of the integrality of the being; (iii) Analyzing the Salesian Social Education as a transformative pedagogical proposal for the 21st century. The corpus selected for this study were the narrative writings of Don Bosco on the Preventive System (1877) and notebooks of the Rede Salesiana Brasil de Ação Social (2016, 2017 and 2018). This decision is justified by the fact that we deepen both conceptual and theoretical contributions of Salesian education, which are relevant to the development of philosophical and methodological principles, aiming to respond to the training needs of social educators who emerge in the context of contemporary society. The theoretical framework that supports this work were the studies on: Social Education by FREIRE (1980), PETRUS (1997) and MULLER (2002 and 2010); on Preventive System in BOSCO (1877 and 1884) and BRAIDO (1993) and the studies on Integral Ecology by FRANCISCO (2015), BOFF (2004) and MURAD (2016). The applied methodology was qualitative based on literature (CONNELLY AND CLANDININ, 2011). The method used was bibliographical research. The expected result consists of an epistemological construction that will allow, in the future, to create methodological and practical subsidies for the formation of social educators based on intentionality, philosophical, and theoretical principles, which are significant for the development of educational praxis in the Salesian perspective of social educators, as well as contributing to the development of educational sciences in its social dimension.(AU)